Moroccan Theatre Building the Nation (London Journal of Research In Humanities and Social Sciences, 2024)
This article is about narrating the nation in the Moroccan theatre.Nation is hardto define and some say it did not exist in the past because of brute force. For me, the intellectually-advanced Islamic Spain emerges as an intercultural, luminary beacon and constitutes a nation. Individuals, nowadays, make the nation by writing about things that truly matter. These individuals have things in common but coloniality made de-territorialization extremely hard. We do not live in imagined communities, but we narrate the nation by theatre with a common cause, and transfer to posterity folklore as heirloom, which aims at preservation of Moroccan culture from historical erasure. Specifically, I will try to talk about how the Moroccan theatre began through al-halka, al-bssat, sayid alkatfii; sultan al-Talba, Ebidat Erma; al-Maddahun; Munshidoo al-Mawloudia and finally Boujeloud. In the modern sense of the word, the Moroccan theatre emerges as narration with its visual effects and stories that tell the Other our shared identity and sense of national belonging, making them live with us in imagined communities, helping us to define and redefine ourselves constantly in what is known as becoming,with the contingencyof historical continuation. I will try to sketch a brief history of the notion nation and relate it to Moroccan theatre. Then, I shall delve into analysis of some aspects of Moroccan theatre in Morocco that helps constitute the modern nation, by blending past and present with a springboard towards the future, and/or consent. I chose to talk about the inception of Moroccan theatre because it is groundedin history. To prove the existence of nation, I will try to talk about the inception of the Moroccan theatre and its strategies of narration. I hope to showhow nation is narrated through theatre. My primary sources are an article entitled, What is a nation? (1886) by Orientalist Ernest Renan (I will try to debunk his ideas); Homi Bhabhas book Nation and Narration (1990) and the book by Mohamed Adib el Slaoui, al-Massrah al-Maghribii: al-Bidaya wa al-imtidad (1996).
Keywords: Gender; domestic violence; Violence; Intersectionality; femicide; fundamental rights; positive obligations; family life; Nation; narration; Morocco; theatre; inception; aspects.